Analisis Faktor-faktor yang Memengaruhi Pendapatan Usahatani Padi (Studi Kasus Gapoktan Lestari Desa Bulakpacing Kecamatan Dukuhwaru Kabupaten Tegal) - Permatasari, Dian Novita; Satriani, Ratna; Mandamdari, Alpha Nadeira (Universitas Galuh, 2024)
Rice farming income, especially in Gapoktan Lestari, has decreased, this is due to a decrease in rice productivity. The purpose of this study is to determine the influence of factors such as land area, selling price, amount of production, level of formal education, level of non-formal education, and length of farming on rice farming income in Gapoktan Lestari. This study used quantitative research methods using cross section data. The results of the study showed that together all variables had a positive and significant effect on rice farming income in Gapoktan Lestari as evidenced by the results of the F test calculation, which was 14661,013 greater than the F table, which was 2.29 and the prob value. F-count (0.000) < alpha 5%. The value of Adjusted R Square = 0.995, means that 99.5 percent of the influence of variables such as land area, selling price, amount of production, level of formal education, level of non-formal education, and length of farming on rice farming income and the remaining 0.5 percent is influenced by other factors. Partially, the variables of land area, selling price, amount of production, non-formal education and length of farming have a positive and significant effect on rice farming income, while formal education has a negative and significant effect on rice farming income in Gapoktan Lestari.